Perception of robotic actions and the influence of gender - Abel, Miriam; Buccino, Giovanni; Binkofski, Ferdinand (Frontiers in Psychology, 2024)
In our society interaction with robots is becoming more and more frequent since robots are not only used in the industry, but increasingly often in assistance and in health system. Perception of robots and their movements is crucial for their acceptance. Here we shortly review basic mechanisms of perception of actions, and then of perception of robotic and human movements.The literature demonstrates that there are commonalities, but also differences in the perception of human and robotic movements. Especially interesting are biologic gender differences in the perception of robotic movements. The results show that males seem to be more sensitive to the differences between robotic and anthropomorphic movements, whereas females seem not to perceive such differences. However, females transfer more anthropomorphic features to robotic movements. While looking at the brain activation during perception of humanoid and robotic movements in different genders one can conclude that different strategies are used; female seem to analyse robotic movements online, while male seem to use previous knowledge from interaction with robots. Further research is needed to specify more such gender differences.Action perception has gained much attention during the last decades. The so-called mirror neuron system (MNS) has been recognized as the major player in action perception, action understanding and action imitation (Rizzolatti & Craighero, 2004). The MNS includes the ventral premotor cortex (vPMC), inferior parietal cortex (IPC), the supplementary motor area (SMA) and to some extent the superior temporal cortex (Di